Crucial Support, Vital Aspirations: The College and Career Aspirations of Rural Black and Latinx Middle School Students in a Community- and Youth-Based Leadership Program - Darris R. Means (Journal of Research in Rural Education, 2019)
This qualitative case study explores college and career aspirations of rural Black and Latinx middle school students in a community- and youth-based leadership program and how various forms of social capital help cultivate and sustain the aspirations of students. Data include student focus group interviews with a total of 14 rural Black and Latinx middle school students; interviews with three adults; and documents, including local school board minutes and local newspaper articles over a six-month period. Findings include how students' career and college aspirations were shaped and supported by various social networks, including family members, teachers, and the community- and youth-based organization in which all student participants were members. In addition, students discussed a commitment to family and paying forward the sacrifi ces of family to motivate their pursuit of aspirations.